Weight Gain and Comorbidities Associated with Oral Second-Generation Antipsychotics: Analysis of Patients with Bipolar I Disorder or Schizophrenia. (April 2022) - Meyer, Jonathan M.; Bessonova, Leona; Friedler, Haley S.; Mortimer, Kathleen M.; Cheng, Harry; Brecht, Thomas; O'Sullivan, Amy K.; Cummings, Hannah; McDonnell, David; Doane, Michael J.
Abstract: Objective: Clinically significant weight gain (CSWG) is associated with increased morbidity and mortality. This study describes CSWG and comorbidities observed in patients with bipolar I disorder (BD-I) and schizophrenia (SZ) after initiating select second-generation antipsychotics (SGAs). Methods: Percent change in weight, CSWG (=7% weight increase), and incident comorbidities within 12 months of treatment were assessed among patients initiating oral SGAs of moderate-to-high weight gain risk using medical records/claims (OM1 Real-World Data Cloud; January 2013-February 2020). Oral SGAs included clozapine (SZ), iloperidone (SZ), paliperidone (SZ), olanzapine, olanzapine/fluoxetine (BD-I), quetiapine, and risperidone. Outcomes were stratified by baseline body mass index and reported descriptively. Results: Among patients with BD-I (N = 9142) and SZ (N = 8174), approximately three-quarters were overweight/obese at baseline. During treatment (mean duration = 30 weeks), average percent weight increase was 3.7% (BD-I) and 3.3% (SZ). Average percent weight increase was highest for underweight/normal weight patients (BD-I = 5.5%; SZ = 4.8%), followed by overweight (BD-I = 3.8%; SZ = 3.4%) and obese patients (BD-I = 2.7%; SZ = 2.3%). Within 3 months of treatment, 12% of all patients experienced CSWG. A total of 11.3% (BD-I) and 14.7% (SZ) of patients developed coronary artery disease, hypertension, dyslipidemia, or type 2 diabetes within 12 months of treatment; development of comorbidities was highest among overweight/obese patients and those with CSWG. Conclusions: Patients who were underweight/normal weight at baseline had the greatest percent change in weight during treatment. Increased comorbidities were observed within 12 months of treatment, specifically among overweight/obese patients and those with CSWG. The magnitude of weight gain and development of comorbidities were similar for patients with BD-I and SZ. Funding: Alkermes, Inc.